Economic development via dam building: The role of the state government in the sarawak corridor of renewable energy and the impact on environment and local communities - Aeria, Andrew (Center for Southeast Asian Studies, 2016)
Since 1970, as a consequence of Malaysia’s New Economic Policy (NEP) and its integration into the global economy, the development achievements and per capita GDP growth of the resource-rich state of Sarawak have been impressive—although not without problems. Since timber and petroleum resources are exhaustible, and there is a concern with finding new sources of growth and revenue, the federal and state governments advocated industrial diversification in 2008 via the development of a multibillion-ringgit regional development corridor called the Sarawak Corridor of Renewable Energy (SCORE). Central to the success of the huge developmental corridor was cheap hydroelectric power (HEP). For the Sarawak government, SCORE’s launch and eventual success were based on the availability of abundant water resources and suitable hydropower dam sites in the state. Yet, SCORE is likely to contribute to further environmental degradation and impact negatively upon the livelihoods and welfare of local communities. This paper examines this recent development trend and its consequences. Specifically, it examines the role of the Sarawak state government in advocating the construction of numerous HEP dams, the role of foreign and local investment in SCORE, and their collective impact upon the environment and local communities. What this paper reveals is the nexus of close relationships that binds key politicians in the state administration with crony businesses associated with foreign-linked contracts that has proven to be destructive socially and environmentally